Vision and trust as vital elements for confronting leadership and govemance crises in Nigeria (2015)
This paper interrogates the leadership-governance matrix that defines the Nigerian situation. It adopts Richard Joseph’s prebendal/clientelistic mode of analysis of political organisation and behavior in Nigeria to interrogate the nature and character of the nation’s leadership. The paper examines the interface between the poor leadership quality of the nation’s political elite and the endemic bad governance that characteristically promotes mass poverty in the midst of abundant natural resources, unrelenting economic crises, kidnapping, terrorism and insurgency. The paper concludes that credence to the leadership and governance deficits in the country can only emerge when the nation’s leaders are driven by clear, political, social and economic vision that can engender the building and sustenance of public trust in both the leadership and the government of the Nigerian state by the diverse groups that constitute the nation.